Mapping conquest the battle maps of Horseshoe Bend - Braund, Kathryn E. Holland 1955- (The University of Georgia Press, 2024)
"In Mapping Conquest, Kathryn H. Braund offers a unique collection of twelve manuscript maps of the Horseshoe Bend battleground, drawn by soldiers in the aftermath of the March 27, 1814 battle. A collection of engraved maps and twentieth-century maps are also included, as are interpretative images of the site. Mapping Conquest quietly reveals the most important fact about the battle: it was an attack by an American army against a defensive position built to protect the inhabitants of a refugee town of Creek men, women, and children, most of whom lost their lives or were enslaved as a result of the battle. More than just a collection of largely forgotten maps, Braund's study provides biographical details about these amateur cartographers and their maps. The hand-drawn maps by soldiers to friends, family, colleagues, and government officials represented a novel way of conveying the army's experience and celebrated their army's astounding success which destroyed the lives of nearly one thousand Creek Indians. The maps also highlight the Creek response to the American invasion and serve as memorials to those Americans who 'did their duty' in defeating the Creeks and the maps reveal the ways in which the dead American officers were memorialized in their own time and continue to dominate interpretative efforts to this day"--